Identification of built environment factors in enhancing bikeability activities in neighbourhoods / Norhazlan Haron, Halmi Zainol and Wan Rabiah Wan Omar - Haron, Norhazlan; Zainol, Halmi; Wan Omar, Wan Rabiah (2021)
The cycling activity has been determined as an active and environmentally-friendly mode of travel and a solution for the urban issues. However, the relationship between the built environment and cycling behaviour is less associated with increasing the bike-ability of the resident's physical activities. The main aim of this research is to identify specific factors that can enhance the level of bike-ability. The objectives of this research are listed as: 1) To designate a particular characteristic of attributes factors that can improve the level of bike-ability; 2) To identify the natural environment factor that influences bike-ability behaviour and 3) To assess the social factor that influences bike-ability behaviour. The questionnaire was derived from the Theory of Planned Behavior from previous studies. The selection of survey variables was determined after a review of several papers published in referenced periodicals. Face validity of the questionnaire was conducted from the selected six experts in cycling development. Four hundred and fifty respondents were selected for this survey. The questionnaire comprised seven personal factors, nine built environment factors, and the respondents are asked to assess the perspectives for cycling behaviour. A Likert scale was used ranging from “Strongly disagree” 1 to “Slightly agree” 5. An in-depth analysis of the cyclist’s perceptions was attempted using confirmatory factor analysis. The Structural Equations Model was estimated to find relationships among variables. The research has found that built environment factors are the essential elements to understand the cycling perceptions and behaviour towards cycling activity.